Unfavorable results in replantation - Abraham G Thomas (Indian Journal of Plastic Surgery)
Reattachment of amputated parts of the body (Replantation) has become a reality since the first arm replant was carried out six decades ago. Failures were not uncommon in the beginning, leading on to the analysis of the problem and refinements in technique. Improvements in sutures, instrumentation and better microscopes further helped the surgeons to do replantation with better finesse and functional results. Evaluation of results and particularly failure and long term results help the younger surgeons to learn from the difficulties faced earlier to do better in the future. An attempt is made to list various aspects of replantation experienced by the author during the past 30 years, particularly in reference to unfavorable results, which had been occasionally total failure, or a partial failure, with poor function and cosmesis due to infection. An insensate limb with poor function is the result of inadequate or improper nerve coaptation or infection destroying the whole repair. It is apt to mention that infection is mostly the result of poor vascularity due to devitalized tissue. Difficulties arise often in identifying the viable tissue, particularly while debriding in the distal amputated part since there is no bleeding. Experience counts in this, specifically to identify the viable muscle. The factors that may lead to complications are listed with remarks to avoid them.